Faktor-faktor yang Berhubungan Dengan Pemkaian AKDR Di Puskesmas Beringin Raya - rizawati; yulia netri (Jurnal Amanah Kesehatan, 2024)
An intrauterine contraceptive device (IUD) is a small device consisting of flexible polyethylene plastic material that is inserted into the uterine cavity, which must be replaced if it has been used for a certain period. This contraceptive is very effective, reversible and long term compared to other contraceptive methods. This research is an analytical research with a cross sectional research design. This research aims to determine the factors related to the use of IUDs at the Beringin Jaya Community Health Center in 2023. The total research sample was 94 people. The data collection method uses primary data, namely by means of structured interviews in the form of questionnaires and secondary data. The data analysis used is univariate analysis and bivariate analysis using the Chi-Square test. The results of the research show that there is no influence between education on the use of IUD contraceptives at the Beringin Jaya Health Center in 2023. There is an influence between knowledge and the use of IUD contraceptives at the Beringin Jaya Health Center in 2023. There is an influence of age on the use of IUD contraceptives at the Beringin Jaya Health Center in 2023. 2023. There is an influence between parity on the use of IUD contraceptives at the Beringin Jaya Community Health Center in 2023. It is hoped that health workers will further improve health promotion, especially education about providing complementary foods for breast milk properly and correctly. Keywords: Factors, IUD